Molluscan models: Crepidula fornicata. (August 2016) - Henry, Jonathan Q.; Lyons, Deirdre C.
Abstract : Gastropod snails in the genus Crepidula have emerged as model systems for studying a metazoan super clade, the Spiralia. Recent work on one species in particular, Crepidula fornicata, has produced high-resolution cell lineage fate maps, details of morphogenetic events during gastrulation, key insights into the molecular underpinnings of early development, and the first demonstration of CRISPR/Cas9 genome editing in the Spiralia. Furthermore, invasive species of Crepidula are a significant ecological threat, while one of these, C. fornicata, is also being harvested for food. This review highlights progress towards developing these animals as models for evolutionary, developmental, and ecological studies. Such studies have contributed greatly to our understanding of biology in a major clade of bilaterians. This information may also help us to control and cultivate these snails.